Strategi Optimalisasi Karyawati dalam Peningkatan Unit Usaha Pesantren Darularafah Raya Deli Serdang - Lubis, Harun; Aulia, Tirta Yogi; Salabi, Agus Salim (Saree: Research in Gender Studies, 2022)
Optimization of female employees is the maximum empowerment of women which is a strategic way for the leadership of Pesantren Darularafah Raya to increase the role of women in the development of pesantren business units as an effort towards the independence of educational institutions. This type of research is qualitative to describe the factors that affect pesantren leaders in optimizing female employees and employee optimization strategies. Collecting data in this study using interview techniques, observation, and document study. Furthermore, the data collected was analyzed in stages: (1) data condensation, (2) data presentation, and (3) conclusion or verification. The findings found six factors that influence Pesantren leadership in optimizing female employees, namely: loyalty; ability to play multiple roles, relatively longer working period (endurance), feeling sufficient (qana'ah) with the welfare and comfort provided, a significant contribution in the Islamic boarding school business unit, active work and able to improve personal and group (family) welfare. Strategies for optimizing female employees in pesantren business units include: 1) opening opportunities and job opportunities, 2) conducting recruitment, 3) living in pesantren, 4) conducting training, 5) conducting mapping, 6) placement, and 7) Refreshment. AbstrakOptimalisasi karyawan perempuan adalah pemberdayaan perempuan secara maksimal yang merupakan cara strategis pimpinan Pondok Pesantren Darularafah Raya untuk meningkatkan peran perempuan dalam pengembangan unit usaha pesantren sebagai upaya menuju kemandirian lembaga pendidikan. Jenis penelitian ini adalah kualitatif untuk mendeskripsikan faktor-faktor yang mempengaruhi pimpinan pesantren dalam mengoptimalkan karyawan perempuan dan strategi optimalisasi karyawan. Pengumpulan data dalam penelitian ini menggunakan teknik wawancara, observasi, dan studi dokumen. Selanjutnya data yang terkumpul dianalisis dengan tahapan: (1) kondensasi data, (2) penyajian data, dan (3) kesimpulan atau verifikasi. Hasil penelitian menemukan enam faktor yang mempengaruhi kepemimpinan pesantren dalam mengoptimalkan karyawan perempuan, yaitu: loyalitas; kemampuan memainkan peran ganda, masa kerja yang relatif lebih lama (daya tahan), merasa cukup (qana'ah) dengan kesejahteraan dan kenyamanan yang diberikan, kontribusi yang signifikan dalam unit usaha pesantren, aktif bekerja dan mampu meningkatkan kesejahteraan pribadi dan kelompok (keluarga). Strategi optimalisasi karyawan perempuan di unit usaha pesantren antara lain: 1) membuka peluang dan kesempatan kerja, 2) melakukan rekrutmen, 3) tinggal di pesantren, 4) melakukan pelatihan, 5) melakukan pemetaan, 6) penempatan, dan 7) Penyegaran.